Освітній кластер як інституціональна основа розвитку регіонального ринку праці - Сибірцев, В. В.; Sybirtsev, V. (Донецький національний університет, 2016)
В статті розглянуто особливості організації освітнього забезпечення формування та розвитку ринку праці на основі безперервного підвищення кваліфікації та перепідготовки трудових ресурсів регіону. Освітній кластер представлено як середовище гармонізації інтересів та інституціоналізації взаємодії суб’єктів регіонального ринку праці в процесі оптимізації його професійно-кваліфікаційної структури. Визначена роль регіонального менеджменту у подоланні диспропорцій регіонального ринку праці та наданих освітніх послуг. Освітній кластер подано як інструмент сприяння реалізації державної політики у сфері зайнятості на регіональному рівні. Представлено модель освітнього кластера та визначено особливості організації взаємодії його учасників із суб’єктами регіонального ринку праці. Визначено систему когнітивних зв’язків між параметрами функціонування освітнього кластеру та вимогами регіонального ринку праці. Розроблена структура механізму інтеграційної взаємодії ринків праці та освіти. Визначено теоретико-методологічний базис використання кластерних механізмів для формування освітнього забезпечення функціонування та розвитку регіональних ринків праці. The article deals with the features of the educational support organizing for the labor market function and development. This support has been based on the continuous training and retraining of the workforce in the region. The education cluster has presented as an environment of interests harmonization and as a tool for institutionalize interaction between the regional labor market participants during the process of this market professional and qualification structure optimization. The role and place of the regional management has determined for the purpose of deleting the disparities between regional labor market and educational services which provided to labor market participants. The education cluster presented as a tool to facilitate implementation of state policy in the field of employment at the regional level. The features of interaction organizing between the educational cluster and regional labor market participants have been shown. The system of cognitive links between the parameters of educational cluster functioning and the requirements of regional labor market determined. The structure of interaction mechanism for labor and education markets integration is developed. The theoretical and methodological basis of cluster mechanism using for the formation of educational support of regional labor markets functioning and development has been determined.
The educational cluster as the institutional framework for the regional labor market development
Keywords: освітній кластер; регіональний ринок праці; підвищення кваліфікації; перепідготовка кадрів; регіональний менеджмент; інтегрована освітня діяльність; теоретико-методологічний базис; educational cluster; regional labor market; qualification improvement; retraining; regional management; integrated educational activities; theoretical and methodological basis